1998
DOI: 10.1021/ic9802552
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Charge-Transfer Photochemistry Clarified by a CASSCF/MR-CCI Comparative Study of the Low-Lying Excited States of M(R)(CO)3(H-DAB) (M = Mn, R = H, Methyl, Ethyl; M = Re, R = H; DAB = 1,4-Diaza-1,3-butadiene)

Abstract: The lowest energy electronic transitions of the model complexes M(R)(CO)3(H-DAB) (M = Mn, R = H, CH3,C2H5; M = Re, R = H, α-diimine = H-DAB = 1,4-diaza-1,3-butadiene) are investigated with the use of CASSCF/MR-CCI calculations. On the basis of the excitation energies calculated for the low-lying nd → π*DAB (metal-to-ligand-charge-transfer), σM - R → π*DAB (sigma-bond-to-ligand-charge-transfer), and nd → nd (metal-centered) excited states, it is shown how the three-center interaction between the R group, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The same behavior was observed for similar Pt‐based dyes 12. Moreover, the replacement of phen by bipy does not change the λ max , but slightly decreases the molar absorptivity of the CT band, while increasing the absorption at 300 nm due to intraligand transitions 13. In line with the above observations, CO stretching frequencies indicate a destabilization of the rhenium‐based HOMO for the alkynyl complexes as compared to neutral or even halide‐type ligands at the sixth position 3c,3e,4c…”
Section: Resultssupporting
confidence: 74%
“…The same behavior was observed for similar Pt‐based dyes 12. Moreover, the replacement of phen by bipy does not change the λ max , but slightly decreases the molar absorptivity of the CT band, while increasing the absorption at 300 nm due to intraligand transitions 13. In line with the above observations, CO stretching frequencies indicate a destabilization of the rhenium‐based HOMO for the alkynyl complexes as compared to neutral or even halide‐type ligands at the sixth position 3c,3e,4c…”
Section: Resultssupporting
confidence: 74%
“…Recent transient UV/Vis and IR absorption measurements [7] indicate that this dissociative 3 oi' state is populated by intersystem crossing from 'MLCT Franck-Condon states so that the 'MLCT state reached by optical excitation must have some t an* character. Indeed, CASSCF ab initio calculations on [Re(H)(CO)3(H-DAB)] confirm that MLCT /6n' mixing occurs [24].…”
Section: Spectroscopic Data and Theoretical Calculations Indicate Thamentioning
confidence: 97%
“…Pioneering studies by Stufkens and co-workers , and Hartl and co-workers , demonstrated that the fac - 1 -(CO)­(X) ( 1 = Mn­(bpy)­(CO) 2 , bpy = 2,2′-bipyridyl, X = halide ion) and related diimine complexes have a rich photochemistry. It was determined that UV irradiation in weakly coordinating solvents resulted in fac → mer photoisomerization and concurrent formation of the dimeric species, [ 1 -(CO)] 2 , formed upon homolysis of the Mn–X bond.…”
Section: Introductionmentioning
confidence: 99%